Force 136 story of a WWII resistance fighter - Chen, Chongzhi 1916- (Asiapac Books, 1995)
Force 136 is the autobiography of a man who swore himself to two missions: first, to defend his homeland during the Japanese Occupation in the early 1940s; second, to make known to everyone the patriotic ardour of the resistance fighters, including the dauntless Lim Bo Seng.To the first cause, author Tan Chong Tee remains faithful, having risked his life in the daredevil stunts required of his calling, and suffered imprisonment and torment to keep the secrecy of the team. As to the second cause, it is his desire that in producing this English edition, readers worldwide will be able to recapture the events of World War II in this region. And his testimony is invaluable since there remain only nine survivors of Force 136 residing in Singapore left to tell their story.